Psychotic-Like Experiences at the Healthy End of the Psychosis Continuum - Unterrassner, Lui; Wyss, Thomas A.; Wotruba, Diana; Ajdacic-Gross, Vladeta; Haker, Helene; Rössler, Wulf (Frontiers in Psychology, 2017)
There is increasing evidence pointing toward a continuous distribution of psychotic symptoms and accompanying factors between subclinical and clinical populations. However, for the construction of continuum models, a more detailed knowledge of different types of psychotic-like experiences (PLE) and their associations with distress, functional impairment, and demographic variables is needed. We investigated PLE in a sample of healthy adults (N = 206) incorporating the recently developed revised Exceptional Experiences Questionnaire (PAGE-R). For the first time, the PAGE-R was cross validated with PLE, disorganized-, and negative-like symptoms [Schizotypal Personality Questionnaire (SPQ), Physical Anhedonia Scale (PAS)]. We subjected the PAGE-R to exploratory factor analyses and examined the resulting subtypes of EE for specific associations with contextual factors, valence ratings, socio-demographic variables, and general psychological burden (Revised Symptom-Checklist-90). Correlational cross-validation suggested that the PAGE-R measures facets of PLE. Importantly, we (1) identified three types of exceptional experiences (EE): Odd beliefs, dissociative anomalous perceptions, and hallucinatory anomalous perceptions. Further, the results suggested that even in healthy individuals (2) PLE and EE are indicative of reduced functioning, as reflected by increased psychological burden and lower educational achievement. Moreover, (3) similar sex-differences might exist as in psychotic patients with women reporting more positive-like symptoms and EE but less disorganized-like symptoms than men. Importantly, (4) EE might be differentially implicated in psychological functioning. We suggest that the PAGE-R holds the potential to complement the current assessment of sub-clinical psychosis. However, whereas our results might point toward a continuity of psychotic symptoms with EE and normal experiences, they require replication in larger samples as well as equivalence testing across the psychosis continuum. Future analyses incorporating the PAGE-R might shed more light onto mechanisms that are implicated in the progress or resilience toward clinical illness.